1990
DOI: 10.1207/s15328023top1702_6
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Psychology Alumni: Gender and Cohort Differences in Course Usefulness, Postbaccalaureate Education, and Career Paths

Abstract: W e surveyed psychology majors who paduated between 1967 and 1986 to investigate gender and cohort differences in curreht perceptions of undergraduate course usefulness, postbaccalaureate education, and occupational achievements. W e found that more women than men (a) obtained bacheh's degrees inpsychology during the 20-year period; (b) earned advanced degrees in psychology and psychology-related fields; and 4c) in recent years, worked in psychology a d psychology-related positions. The two courses most freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…The positive overall ratings provided for perceived level of knowledge of cultural and individual diversity, and experimental, applied, and ethical areas of psychology indicate the majors' perceived knowledge base in psychology is good. Similar to Keyes and Hogberg's (1990) findings, alumni rated a variety of specific courses in the psychology curriculum, including the Research Sequence, as useful in their jobs. Favorable ratings were provided by most seniors in response to their critical thinking skills and written and oral communication skills and how much they learned from specific courses; this finding provides evidence that PSYCHOLOGY DEGREE PROGRAM Bickes, Lawrence, and Noble students perceive the quality of the program as good.…”
Section: Discussionsupporting
confidence: 69%
“…The positive overall ratings provided for perceived level of knowledge of cultural and individual diversity, and experimental, applied, and ethical areas of psychology indicate the majors' perceived knowledge base in psychology is good. Similar to Keyes and Hogberg's (1990) findings, alumni rated a variety of specific courses in the psychology curriculum, including the Research Sequence, as useful in their jobs. Favorable ratings were provided by most seniors in response to their critical thinking skills and written and oral communication skills and how much they learned from specific courses; this finding provides evidence that PSYCHOLOGY DEGREE PROGRAM Bickes, Lawrence, and Noble students perceive the quality of the program as good.…”
Section: Discussionsupporting
confidence: 69%
“…One of our psychology major’s written comments during the study reflects an important reason to share career information with prospective and current students; she said, “people are scared to go into psych, in fear of graduating and not getting a job.” As Ware and Meyer (1981) concluded, “The evidence does not support the views that bachelor-level psychology graduates cannot find a job and that the available occupations for psychology graduates are in only the human service areas” (p. 14). The results of surveys of psychology graduates (e.g., Keyes & Hogberg, 1990; Landrum, 2009; Quereshi, 1988; Ware & Meyer, 1981) and the alumni profiles we have obtained of our graduates during the past 20 years illustrate the diversity of careers obtained by psychology graduates. As Lawson, Jordan-Fleming, and Upton (1997) pointed out, “these surveys have shown that, in addition to jobs in human services, psychology graduates find employment in areas such as management, sales, marketing, personnel, and education” (p. 201).…”
Section: Discussionmentioning
confidence: 68%
“…For example, many of our alumni emphasize the usefulness of our research courses (i.e., Research I, Research II, and Senior Thesis), even for careers that might not seem closely related to research (e.g., teacher, therapeutic service provider). Similarly, Keyes and Hogberg (1990) found that their alumni reported methodology courses as some of the most useful courses. Reading this information from alumni might help current students understand the value of research courses, which they may view as more tedious and less interesting than other courses.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…First, male graduates have been more likely than their female counterparts to be employed in business-related occupations (Keyes & Hogberg, 1990;Lunneborg & Wilson, 1985;Titley, 1978;Ware & Meyer, 1981 ). First, male graduates have been more likely than their female counterparts to be employed in business-related occupations (Keyes & Hogberg, 1990;Lunneborg & Wilson, 1985;Titley, 1978;Ware & Meyer, 1981 ).…”
Section: Review Of Alumni Survey Literaturementioning
confidence: 99%